Influence of Abrasive Water Jet (AWJ) on Surface Roughness (International Journal of Engineering Materials and Manufacture, 2021)
Abrasive water jet (AWJ) is one of the most advanced and valuable non-traditional machining processes because of its massive advantages of removing metals ranging from hard to soft. This paper focused on studying the influence of jet pressure, feed rate and standoff distance on surface roughness during cutting carbon steel using abrasive water jet cutting. A surface roughness device assessed the surface roughness by performing sixteen experiments to identify the distinct texture of the surface. Based on the experiences, the best surface roughness value was 3.14 Î¼m at jet pressure 300 MPa, standoff distance 4mm and feed rate 30 mm/min. The Taguchi method was introduced to implement the experiments and indicate the most influential process parameters on average surface roughness. The experimental results reveal that feed rate has a significant effect on average surface roughness.